Contemporary art in Belgium 2006 - Bounameaux, Henry; De Baere, Bart (Brussel : Best of Publishing Brussel, 2005)
Bock, John ; Brouwn, Stanley ; Colson, Vaast ; Dans, Michael ; Denicolai, Simona ; Dietvorst, Els ; Fink, Christoph ; François, Michel ; Geers, Kendell ; Geyskens, Vincent ; Gonzalez-Foerster, Dominique ; Van Imschoot, Jan ; Kemps, Niek ; Körmeling, John ; Kusolwong Surasi ; Marisaldi, Eva ; Mik, Aernout ; Van Obberghen, Vanessa ; Opie, Julian ; Pacquée, Ria ; Paparella, Juan ; Provoost, Ivo ; Sierra, Santiago ; Van Snick, Philippe ; Stolle, Bart ; Swennen, Walter ; Theys, Koen ; Tordoir, Narcisse ; Torfs, Ana ; Tuymans, Luc ; Venlet, Richard ; Verhoeven, Gert ; Wéry, Marthe
boek
Keywords: België